Correction: Artificial testis: a testicular tissue extracellular matrix as a potential bio-ink for 3D printing - Bashiri, Zahra; Amiri, Iraj; Gholipourmalekabadi, Mazaher; Falak, Reza; Asgari, Hamidreza; Maki, Chad B; Moghaddaszadeh, Ali; Koruji, Morteza (Biomaterials science, 2025)
Correction for 'Artificial testis: a testicular tissue extracellular matrix as a potential bio-ink for 3D printing' by Zahra Bashiri et al., Biomater. Sci., 2021, 9, 3465-3484, https://doi.org/10.1039/D0BM02209H.Correction for 'Artificial testis: a testicular tissue extracellular matrix as a potential bio-ink for 3D printing' by Zahra Bashiri et al., Biomater. Sci., 2021, 9, 3465-3484, https://doi.org/10.1039/D0BM02209H.